2021
DOI: 10.1039/d1nr01328a
|View full text |Cite
|
Sign up to set email alerts
|

Emerging carbon shell-encapsulated metal nanocatalysts for fuel cells and water electrolysis

Abstract: Carbon shell encapsulated metal nanoparticles (M@C) are key materials for fuel cell and water electrolysis applications. This review highlights the current challenges and future prospects of M@C electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 199 publications
0
37
0
Order By: Relevance
“…For example, a Pt@C core-shell catalyst was developed, in which graphitic-and pyridine-N on the carbon shell together with Pt nanoparticles served as the active sites for HER. [167,168] Benefited from this specific structure, the carbon shell could not only effectively prevent the dissolution and agglomeration of Pt core, but also allow the facile transport of reactants, improving mechanical stability and minimizing the loss of catalytic activity. In addition, it was also found that the peeling-off issue would become more serious if the interaction between catalyst and support was weaker than the interfacial adhesion force between the catalyst and the bubble.…”
Section: Effect Of Industrial Reaction Conditions On Catalystsmentioning
confidence: 99%
“…For example, a Pt@C core-shell catalyst was developed, in which graphitic-and pyridine-N on the carbon shell together with Pt nanoparticles served as the active sites for HER. [167,168] Benefited from this specific structure, the carbon shell could not only effectively prevent the dissolution and agglomeration of Pt core, but also allow the facile transport of reactants, improving mechanical stability and minimizing the loss of catalytic activity. In addition, it was also found that the peeling-off issue would become more serious if the interaction between catalyst and support was weaker than the interfacial adhesion force between the catalyst and the bubble.…”
Section: Effect Of Industrial Reaction Conditions On Catalystsmentioning
confidence: 99%
“…As an alternative strategy, our research group has intensively studied the fabrication of carbon shell-encapsulated metal nanoparticles for fuel cell applications. [25][26][27][28] The ultrathin carbon shells formed on metal nanoparticles generally have a robust structure that can withstand structural degradation for thousands of potential cycles. However, the development of fine-control technology of carbon shell structures for electrochemical applications remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the electronic properties of the carbon shell can be modulated by the metallic nanoparticle cores, allowing for the binding energies of reaction intermediates on the carbon surface to be tuned. In some cases, carbon encapsulated metal nanoparticles exhibit high activity simultaneously against a variety of electrochemical reactions (e.g., HER and OER), demonstrating a bi-functional catalyst [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods, such as chemical vapor deposition (CVD), the polymer coating method, the solvothermal method, and the hightemperature pyrolytic method, have been utilized to form a thin carbon shell to encapsulate metal nanoparticles. Among all these, the solvothermal method has been given the most interest due to several advantages including a low temperature process ( < 300 • C), morphology tuning, time-efficient, possible scale-up, possibility of engineering the carbon shell, and so forth [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation